Sanford Underground Research Facility’s approach to school education, community activities, and public outreach - Horn, Markus; Woodward, Erin Lorraine (Frontiers in Physics, 2023)
The Sanford Underground Research Facility (SURF) is the deepest underground science facility in the United States. SURF hosts world-leading experiments in neutrino, astroparticle and nuclear physics, as well as projects in biology, geology, and engineering, and is home to a major excavation project making space for Fermi National Accelerator Laboratory’s Long-Baseline Neutrino Facility (LBNF), which will power the Deep Underground Neutrino Experiment (DUNE). An emphasis on outreach and education is embedded in SURF’s mission statement: “to advance world-class science and inspire learning across generations.” To achieve this mission, SURF goes beyond established science communication methods, including operating an open-to-the-public visitor center, hosting multiple public outreach events per month, and an annual city-wide science festival. Furthermore, SURF is training K-12 science educators, developing school curriculum units, and providing classroom materials, based on science researched at the laboratory. The strategic approach, specific methods, and successful outcomes of these programs, which are based on SURF’s science, location, and community, may serve as examples for effective science education, public outreach, and community engagement.